2021
DOI: 10.18251/ijme.v23i1.2463
|View full text |Cite
|
Sign up to set email alerts
|

From Google Searches to Russian Disinformation: Adolescent Critical Race Digital Literacy Needs and Skills

Abstract: This study uses a Critical Race Digital Literacy framework to examine Black and Latinx adolescents’ ability to critically evaluate race-related materials online. Participants completed four tasks that required them to engage with a range of race-related material, from search results to social media content. Findings indicate that the majority of participants demonstrated an “emerging” or “mastery” level understanding of search results and determining the trustworthiness of websites. Participants found evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…Healthy data practices in this context include realistic caution and awareness of these nefarious possibilities. Beyond simple “mistrust,” these practices need to develop more robust modes of scepticism, self‐awareness, and proactive stances like those of P1, P5 and P6, and like the activist roles described by Tynes et al (2021).…”
Section: Discussion: Implications For Data Literacy Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthy data practices in this context include realistic caution and awareness of these nefarious possibilities. Beyond simple “mistrust,” these practices need to develop more robust modes of scepticism, self‐awareness, and proactive stances like those of P1, P5 and P6, and like the activist roles described by Tynes et al (2021).…”
Section: Discussion: Implications For Data Literacy Educationmentioning
confidence: 99%
“…This management, especially of internal resources, is akin to the psychological notion of self-regulation (eg, Azevedo et al, 2017). In particular, in the present analysis we highlight two resources emphasized in research on public engagement with data and online information: trust (Hendriks et al, 2016(Hendriks et al, , 2020Tynes et al, 2021), and emotion (Garcia et al, 2021;Kahan, 2017;Sinatra & Seyranian, 2016). Each is briefly reviewed below.…”
Section: Management Of Resources In Data Literacymentioning
confidence: 97%
See 1 more Smart Citation
“…The application of CRT to the field of education has allowed for a broad systems analysis of educational laws and policies and has faced recurring and renewed resistance from political opponents. These critical analyses of race extend into the online learning space as well; where Tynes et al (2021) put forth critical race digital literacy (CRDL) as a way for youth to understand race-related media and technology. The development of critical consciousness through a systemic analysis of technologies is an inherent feature of Afrofuturist development.…”
Section: Critical Consciousness and Action Are Competencies Taught In...mentioning
confidence: 99%
“…An Afrofuturist Developmental lens leverages the benefits of critical consciousness by highlighting the ways that racism is embedded in technology and how culturally-specific practices with media can serve liberatory purposes for Black youth. For instance, Tynes et al (2021) found that youth, in general, have a wide range of ability levels in detecting racialized mis/disinformation from algorithms, to websites, to social media posts. For Black youth in particular, teachers can begin developing their critical consciousness and CRDL early by providing lessons about algorithmic erasure and bias against Black women, encouraging sound critique of news sites reporting of Black social movements, and vetting information from influential figures and organizations.…”
Section: Critical Consciousness and Action Are Competencies Taught In...mentioning
confidence: 99%